1999
DOI: 10.1007/pl00013904
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Development, and Auxin Polar Transport in Higher Plants under Microgravity Conditions in Space: BRIC-AUX on STS-95 Space Experiment

Abstract: The principal objectives of the space experiment, BRIC-AUX on STS 95, were the integrated analysis of the growth and development of etiolated pea and maize seedlings in space and a study of the effects of microgravity conditions in space on auxin polar transport in these segments. Microgravity significantly affected the growth and development of etiolated pea and maize seedlings. Epicotyls of etiolated pea seedlings were the most oriented toward about 40 to 60 degrees from the vertical. Mesocotyls of etiolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
77
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 16 publications
12
77
1
Order By: Relevance
“…Heathcote et al (1995) showed that wheat coleoptiles oriented away from the caryopsis (abaxial). Pea epicotyls also oriented abaxial direction (Ueda et al, 1999). On the other hand, rice coleoptiles bended adaxial direction toward the caryopsis (Hoson et al, 1999).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Heathcote et al (1995) showed that wheat coleoptiles oriented away from the caryopsis (abaxial). Pea epicotyls also oriented abaxial direction (Ueda et al, 1999). On the other hand, rice coleoptiles bended adaxial direction toward the caryopsis (Hoson et al, 1999).…”
Section: Resultsmentioning
confidence: 97%
“…These results indicate that growth pattern of shoots in space is different by plant species and by the type of organs. Epicotyls of both pea (Ueda et al, 1999) and azuki bean (Fig. 1) elongated abaxially in space.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxin polar transport was determined according to the method reported previously (Oka et al, 1995;Ueda et al, 1999Ueda et al, , 2000Ueda et al, , 2012Ueda et al, , 2013Hoshino et al, 2007) , American Radiolabeled Chemicals Inc., St. Louis, Mo.) was prepared in 1.5 ml Eppendorf tubes, and was incorporated into the apical or the basal side of the segments in the tube.…”
Section: Determinations Of Auxin Polar Transportmentioning
confidence: 99%
“…These circumstances can involve a three-dimensional clinostat for simulating microgravity, an agravitropic mutant, or the microgravity conditions of space or parabolic flight. A number of Japanese studies on plant gravitational biology have been conducted aboard the space shuttle, and considerable information about graviperception, growth, and gravimorphogenesis has been obtained (Hoson et al, 1999;Takahashi et al, 2000;Ueda et al, 1999;Wolverton et al, 1999).…”
Section: Introductionmentioning
confidence: 99%